MEMBUMIKAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM KELUARGA DI-ERA GLOBALISASI - Ruqoiyah Ruqoiyah (JIE (Journal of Islamic Education), 2018)
Education is a conscious and planned effort to realize the atmosphere, learning process and learning process so that students actively develop their potential to have religious spiritual strength, self-control, intelligence, noble character, and skills, which are needed by themselves, the nation and the state. The National Education Objective is "developing capabilities and forming dignified national character and civilization in order to educate the nation's life, aiming at developing potential students to become believers and devoted human beings, noble, healthy, knowledgeable, capable, creative independent, and become a democratic and responsible citizen”.